Fruit development of two high oleic safflower (Carthamus tinctorius L.) cultivars - Franchini, Maria Clara (2014)
The purpose of this study was to describe fruit development in two high oleic safflower (Carthamus tinctorius L.) cultivars during four growing seasons. Pericarp histogenesis, and dynamics of pericarp and seed dry weight and fruit water content were studied. The dynamics of the pericarp and seed growth was similar between cultivars and years. The pericarp completed its growth before the seed. Pericarp potential size was already set at anthesis as no cell division was observed at this time. Maximum pericarp dry weight was achieved 8 days after anthesis, when cell wall lignification concluded. At this time, twinned prismatic simetric crystals had decreased in number and size respect to those observed at anthesis. Physiological maturity (maximum seed dry weight) was achieved between 17 and 25 days after anthesis. Similar pericarp growth rate and duration between cultivars and years were associated to similar maximum pericarp dry weight (17 mg), except in 2012. In this year, the higher maximum pericarp dry weight (20 mg) was only associated to a higher fruit volume (50 µL). Maximum seed dry weight (22 mg) was lower in CW88 OL than in CW99 OL, except in 2012. However, seed growth rate and time of physiological maturity were similar between cultivars. Fruit water content at physiological maturity (39%) was similar between cultivars. The recommended moisture (10-13%) at harvesting was achieved around 33 days after anthesis. The timing of the different morphological and histological events of safflower fruit development presented in this work sets a not-yet-existent conceptual framework, and constitutes an important tool for the interpretation and comparison of the effects of genotype, environment or agricultural management practices on crop yield and fruit quality.